Simulation of a biogas cleaning process using different amines - Sepúlveda, Guillermo; Jaimes, Luis Eduardo; Pacheco, Leonardo; Díaz, Carlos Alirio (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The use of biogas generated in landfills has gained importance in developing countries like Colombia. Taking into account that this biogas presents poor combustion properties that make interchangeability with other combustible gases difficult, the elimination of gases and vapors, such as CO2 and H2O, through a cleaning process, in which the biogas is converted to biomethane, improves the biogas properties as a fuel gas for general use. In this work, we simulated the generation of biogas at El Carrasco sanitary landfill in Bucaramanga, using the US EPA (United States Environmental Protection Agency) landfill gas emissions model. Additionally, we simulated the biogas cleaning process to extract the remaining moisture using the ProMax software; for this, we used three different amines (MDEA, MEA, and DEA), followed by a glycol dehydration process. The results showed that the amine MEA produced the largest increase in the concentration of CH4 (90.37 %) for the biogas generated in the landfill. Furthermore, dehydration with glycol was an efficient process to obtain a gas with a high percentage of methane (91.47 %) and low water presence (1.27 %); this would allow the use of biomethane in conventional industrial combustion processes and power generation.